Co-cultivation of Streptomyces and microalgal cells as an efficient system for biodiesel production and bioflocculation formation. (July 2021) - Lakshmikandan, M.; Wang, Shuang; Murugesan, A.G.; Saravanakumar, M.; Selvakumar, G.
Graphical abstract: Highlights: Co-cultivation system promoted biomass (29%) and lipid productivity (57%). Elevated IAA production (82–140%) was recorded in co-culture system. Late exponential phase Trp stress (1.6 µg mL −1 ) encouraged 21% lipid production. Trp stress reduced 13% of SFA and increased PUFA ratio by 56% in FAMEs profile. Combination of co-culture system and bioflocculation saved 148% energy input. Abstract: The phytohormone producing Streptomyces rosealbus MTTC 12, 951 (S.R) and green microalga Chlorella vulgaris MSU-AGM 14 (C.V) were cultivated in co-culture system to evaluate exogenous hormonal activity. Biosynthesis of indole-3-acetic acid (IAA) and their precursors were quantitatively evaluated by employing High Performance Liquid Chromatography (HPLC). The concentration of IAA (0.72 ± 0.02 µg mL −1 ) was observed to be elevated in co-cultivation system due to symbiotic interaction between Streptomyces and microalgae. In exchange, microalgae produced adequate volume of tryptophan (Trp) to induce IAA biosynthesis. The Trp stress in late exponential phase encouraged lipid accumulation (175 ± 10 mg g −1 ). The bioflocculation property of microalgae ensures potential and economic viable harvesting process by reducing 148% input energy compared to conventional method. The overall results evidenced that C.V co-cultivation with S.R exhibits promotional behavior and serves as a promising cultivation process for microalgae in terms of cost efficiency and energy conservation.